Effect of whole-body vibration combined with exercise therapy on jump-landing stability after ACL reconstruction: A randomized controlled trial - Roya Khanmohammadi; Zahra Rostampour (PLoS ONE, 2026)
This study examined whether incorporating whole-body vibration (WBV) into routine exercises enhances dynamic postural stability during jump-landing in athletes following anterior cruciate ligament reconstruction (ACLR), compared to routine exercises alone. Additionally, the study evaluated the effects of WBV on dynamic balance using the Y-Balance Test (YBT) and on physical performance using the Limb Symmetry Index (LSI) derived from the 6-meter timed hop test.In this randomized, single-blind, controlled trial, thirty participants were assigned to either a WBV plus exercise group or an exercise-only group. Assessments were conducted before and after the intervention. Primary outcomes included the Stability Index (SI) and Time to Stabilization (TTS). Secondary outcomes included the YBT and the LSI.In the WBV group, anteroposterior (AP) TTS decreased significantly (P = 0.001, η² = 0.568), indicating a large effect, while the control group showed no significant change (P = 0.138, η² = 0.150). A similar pattern was found for resultant TTS: the intervention group demonstrated a significant decrease (P = 0.001, η² = 0.533), whereas the control group did not (P = 0.145, η² = 0.146). These findings indicate that TTS decreased significantly only in the WBV group, both in the AP direction and in the combined (resultant) measure. For the YBT (P ≤ 0.016, η² ≤ 0.542) and LSI (P < 0.001, η² = 0.610), both groups demonstrated significant improvements from pre- to post-intervention, with no significant main effects of group or time × group interactions, indicating comparable changes over time. Overall, the study showed that adding WBV to routine exercises produced selective benefits, with additional improvements observed only in TTS during the jump-landing task. In contrast, both groups demonstrated comparable improvements in YBT, and LSI, with no between-group differences. These findings indicate that WBV did not provide added benefit beyond exercise alone for these latter outcomes. Trial registration number : Iranian Registry of Clinical Trials (IRCT20220226054122N1) Registered on 01/03/2022 ( https://irct.behdasht.gov.ir/trial/62172 ).